2014
DOI: 10.1136/gutjnl-2014-306931
|View full text |Cite
|
Sign up to set email alerts
|

The HLA-DQ2 genotype selects for early intestinal microbiota composition in infants at high risk of developing coeliac disease

Abstract: The genotype of infants at family risk of developing CD, carrying the HLA-DQ2 haplotypes, influences the early gut microbiota composition. This finding suggests that a specific disease-biased host genotype may also select for the first gut colonisers and could contribute to determining disease risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
190
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 262 publications
(210 citation statements)
references
References 45 publications
13
190
0
7
Order By: Relevance
“…7 , 8 Besides, we observed that infants with a high genetic risk (HLA-DQ2) had a higher relative abundance of Proteobacteria, and of unclassified Enterobacteriaceae. 8 However, all the preceding studies were taxonomy-based, and the pathogenic potential of the increased abundance of the family Enterobacteriaceae remained unexplored. Here, we describe that, at 4 months of age, the infants with the highest genetic risk of CD development showed a higher prevalence of ETEC, irrespective of milk feeding practices, although this result was only detected by applying a Chi-square test and was not corroborated by the CRT analysis.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…7 , 8 Besides, we observed that infants with a high genetic risk (HLA-DQ2) had a higher relative abundance of Proteobacteria, and of unclassified Enterobacteriaceae. 8 However, all the preceding studies were taxonomy-based, and the pathogenic potential of the increased abundance of the family Enterobacteriaceae remained unexplored. Here, we describe that, at 4 months of age, the infants with the highest genetic risk of CD development showed a higher prevalence of ETEC, irrespective of milk feeding practices, although this result was only detected by applying a Chi-square test and was not corroborated by the CRT analysis.…”
Section: Discussionmentioning
confidence: 72%
“…Correlation analysis of our previous data shows negative associations between Bifidobacterium and Clostridium , and between Bifidobacterium and Escherichia/Shigella . 8 Then, it can be hypothesized that the higher prevalence of C. perfringens and C. difficile , and of enterotoxigenic E. coli might be a consequence of the reductions in Bifidobacterium numbers as previously observed in formula-fed infants and the carriers of the HLA-DQ2 genotype. 7 , 8 Unravelling which is the cause or the consequence, as well as the mechanisms that favor the colonization of certain bacterial groups and the co-exclusion of others should be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The microbiota development is affected by a number of factors including genetics, mode of delivery and gestational age, antibiotic usage, breast feeding (BF)/formula feeding and long-term diet after weaning (Penders et al, 2006;Grönlund et al, 2007;Dominguez-Bello et al, 2010;Ladirat et al, 2013;Azad et al, 2014;Nylund et al, 2014;Olivares et al, 2014;Voreades et al, 2014). During the colonization process, facultative anaerobic bacteria, such as Enterobacteria, are gradually replaced by anaerobic bacteria, such as the genera Bifidobacterium, Clostridium and Bacteroides (Weber and Polanco, 2012;Matamoros et al, 2013;Arrieta et al, 2014).…”
Section: Introductionmentioning
confidence: 99%